Perancangan Sistem Informasi Peminjaman Dan Pengembalian Buku Perpustakaan Menggunakan Barcode Untuk Mendukung Peningkatan Literasi Siswa - Ananda Intan Pratiwi; Asrul Azhari Muin; Izmy Alwiah Musdar (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the low literacy interest of students at SMAN 8 Gowa which has an impact on low library utilization, as well as the continued use of a manual system in managing book borrowing and returns. This study aims to design and implement a web -based Library Book Borrowing and Return Information System and barcode scanning to improve service efficiency and student reading interest. The research methods used include observation, interviews, and literature studies, while the system development applies the Agile method. The system was tested using the blackbox method and compared book borrowing data before and after implementation. The results of the study showed a significant increase in the average book borrowing, from 0.77 books per day before the system was implemented to 3 books per day in June, and increased again to 7 books per day in July, with an overall percentage increase of 808.44%. The implementation of this system not only speeds up the administrative process and minimizes recording errors, but also proves to be able to encourage students' reading habits through the recommendation feature and book synopsis notifications. The implementation of this system not only speeds up the administrative process and minimizes recording errors but also proves to be able to encourage students' reading habits through the recommendation feature and book synopsis notifications. The barcode scanning feature, in particular, allows for faster and more accurate book tracking, making the borrowing process more convenient for students. Additionally, the system provides real-time updates on available books, helping students easily find the materials they need. The increased borrowing activity is a positive sign of the system's effectiveness in improving students' engagement with the library. The system’s user-friendly interface also contributes to its success, making it easier for students and library staff to manage transactions.